The Role of Star Link Mission on Degrading Authoritarian Governments’ Power Across the Middle East - Omid Vatandoost; Elham Salehi (Journal of Management Practices, Humanities and Social Sciences, 2020)
This article seeks to represent the role of Star Link mission about the internet which leads to access without any surveillance by authoritarian governments in the region. The Space X Company launches its mission under the name Star Link. Its mission is to send satellites to space in order to crumble many borders and limitations of accessing to the internet across the world. The question of this article is that how did authoritarian governments control the media? And what can they do after the completion of the Star Link mission? This study is qualitative in nature. Author relied on secondary sources such as journal articles, periodicals, books and websites for data retrieval. The analysis highlights that Star Link strives to establish a new platform of the internet which is based on satellite signals from outside the globe which no more government can put any surveillance on it and no limitation will be in front of its users Current study establishes that if this mission accomplishes its goals, it would be a huge danger for the authoritarian governments which may even lead to the overthrow of governments via shutting down the internet or interfering in it. The findings could be useful for governments to manage their rules and regulations and manage due control on their resources.